THE SITUATION OF SAFETY MANAGEMENT FROM CHEMOTHERAPY DRUGS, SURATTHANI HOSPITAL - Supantee, Supaporn; Thiengchanya, Pratyanan; Purinthrapibal, Shutiwan (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2024)
The purpose of this qualitative research was to study the safety management situation from chemotherapy drugs in Surat Thani Hospital the informants were people involved with chemotherapy, a total of 30 people, selected purposively consisting of 5 administrators, 13 practical registered nurses, and nursing assistants. and 5 patient assistants, 1 building employee, 2 chemotherapy drug delivery staff, and 4 service recipients using standard safety management concepts for giving chemotherapy drugs. of the National Cancer Institute (2022) data were collected using semi-structured interviews. and document review data were analyzed by content analysis. Results of a study of the standard situation of safety management of chemotherapy drugs according to standards 1) Personnel. It was found that personnel lack awareness. not following guidelines lack of continuous review and supervision. less communication in the team 2) The location was found to be crowded, not conducive to work, and not safe 3) Service recipients (patients) found that health education and knowledge assessment including giving advice to patients and relatives Before giving chemotherapy is important. Because if patients and relatives lack knowledge and do not follow guidelines and standards it will affect both patients and relatives. Including operating personnel. Results of this study reflects the necessity of developing a management model for safety from chemotherapy drugs to be consistent with the context of the agency.